PENINGKATAN KETERAMPILAN MEMBUAT TOPENG DENGAN PENERAPAN MODEL PEMBELAJARAN LANGSUNG BAGI SISWA KELAS V SEKOLAH DASAR - Fitrisa, Mega (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This researchoriginated fromthe factthat the learning skillsin make a material of art in the elementary schoolis only regardless withtheassessment of the resultswithout regardless the process how the material of art was made. The problem can repair by using themodel ofdirect instruction. Directinstructional modelis amodel oflearning whichstudents are taughtwithdemonstrations, exercises andassignedgiven the opportunityto make something. This research used qualitative and quantitative approach. The type of this research is action research class with two cycles, consisting of preparation, implementation, observation and reflection in every cycles. The results showed that model ofdirect instruction can increase students' ability to making masks in fifth class. The result for the preparation in first cycle is 80, and for the second one is 95. The increase for teacher activities is 77.5 and 92.5. The increase for students’ activities is 67.5and 88.5. Assessmentof studentsin the first cycleandsecond cyclealso increasedwhere theaverage value of68.54studentsin the first cycle, increasing to 82.97in the second cycle. It can be concludedthat thedirectteaching modelto improvestudents' skills inmakingmasksin classVSDN 12KotoHilalang Kabupaten Agam. Kata Kunci: pembelajaran keterampilan; pembelajaran langsung